The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.1371/journal.pone.0234675
|View full text |Cite
|
Sign up to set email alerts
|

Species composition and risk of transmission of some Aedes-borne arboviruses in some sites in Northern Ghana

Abstract: Aedes-borne viral diseases mainly Yellow Fever (YF), Dengue (DEN), Zika (ZIK) and Chikungunya (CHK) have contributed to many deaths’ in the world especially in Africa. There have been major outbreaks of these diseases in West Africa. Although, YF outbreaks have occurred in Ghana over the years, no outbreak of DEN, ZIK and CHK has been recorded. However, the risk of outbreak is high due to its proximity to West African countries where outbreaks have been recently been recorded. This study surveyed the mosquito … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…Temperature, relative humidity and nutrients source is known to contribute to mosquito abundance during rainy season, while absence of all or any of these components and high or extreme temperature decrease mosquito breeding or abundance in the dry season [33]. In this study, high abundance of Aedes immature stages were found in the rainy season than the dry season as previously reported in other studies in northern and southern Ghana [16] [24] [25]. However, another study in northern Ghana found high larval indices in the dry season than the rainy season and ascribed the reason that many people tend to store water much longer during the dry season than the rainy season [34].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Temperature, relative humidity and nutrients source is known to contribute to mosquito abundance during rainy season, while absence of all or any of these components and high or extreme temperature decrease mosquito breeding or abundance in the dry season [33]. In this study, high abundance of Aedes immature stages were found in the rainy season than the dry season as previously reported in other studies in northern and southern Ghana [16] [24] [25]. However, another study in northern Ghana found high larval indices in the dry season than the rainy season and ascribed the reason that many people tend to store water much longer during the dry season than the rainy season [34].…”
Section: Discussionsupporting
confidence: 81%
“…Different species of Aedes mosquitoes, which are potential vectors for yellow fever, are already known to be distributed all over Ghana as reported by various studies in different parts of the country [11] [16] [24] [25]. The study revealed the presence of only one distinct Aedes species and other mosquito species (Culex spp.…”
Section: Discussionmentioning
confidence: 93%
“…The intense rainfall and flooding activities in the coastal state of Lagos may disrupt the stability of the mosquito eggs and larvae [ 54 ], whereas the forested regions provide more vegetation cover and high relative humidity to support mosquito breeding. Aedes aegypti , the primary vector for DENV, thrives well in urban and semi-urban environments, breeding in stagnant water and hollow containers [ 55 ]. The presence and distribution of Aedes spp.…”
Section: Discussionmentioning
confidence: 99%
“…africanus may have been the vector [ 21 ]. Later, other entomological investigations were done to assess the status and risk of transmission of mosquito-borne viruses [ 44 , 45 , 46 ]. Overall, no arbovirus was detected in any of these entomological studies.…”
Section: Discussionmentioning
confidence: 99%